A New Approach to Supplier Selection: Interval Ranking of DEA with Double Frontiers - Feloora Valizadeh Palang Sarae (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Choosing a set of suppliers is critical to the success of organizations. Effective selection and evaluation of suppliers is an essential responsibility that purchasing managers should always consider. The criticality of supplier selection is due to its effects on elements related to the end products of organizations. Suppliers are a vital part of an organization that can significantly impact an organization's performance. Methodology: In this study, a data set containing the specifications of 18 suppliers. First, the performance of suppliers is calculated from both optimistic and pessimistic perspectives in the presence of undesirable outputs and inaccurate data, and the interval ranking method is used to identify the supplier with the best performance. Findings: The results showed that the traditional DEA method measures only the best relative efficiency of a group of decision-making units while avoiding pessimistic performance. The DEA method for dual boundaries was used to use DEA best and avoid complex mental calculations.  Originality/Value: This paper uses interval ranking and data envelopment analysis with dual boundaries in the presence of undesirable outputs and inaccurate data. In this paper, it is suggested that the calculation of overall efficiency and ranking of suppliers in the model proposed by Azizi et al. (2016) integrate both performance in the form of an interval and the overall efficiency and ranking of units based on Hosseinzadeh et al. (2018) ranking method.